1986
DOI: 10.1007/bf02386643
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic identification of ingested disc batteries

Abstract: Recently, the hazards posed by the accidental ingestion and impaction of small disc batteries have been widely publicized in the medical and lay press. These foreign bodies, when lodged in the esophagus, leak a caustic solution of 26 to 45% sodium or potassium hydroxide which can cause a burn injury to the esophagus in a very short period of time. Because of the considerable clinical morbidity and mortality from this foreign body, it becomes imperative for the radiologist to quickly and accurately identify dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…4 A study involving both radiologists and otolaryngologists reported the combined sensitivity of anteroposterior and lateral plain films in identifying disc batteries to be 80.4 per cent. 5 Underpenetrated films prevented visualisation of a double shadow and significantly reduced the correct identification of batteries.…”
Section: Discussionmentioning
confidence: 99%
“…4 A study involving both radiologists and otolaryngologists reported the combined sensitivity of anteroposterior and lateral plain films in identifying disc batteries to be 80.4 per cent. 5 Underpenetrated films prevented visualisation of a double shadow and significantly reduced the correct identification of batteries.…”
Section: Discussionmentioning
confidence: 99%
“…A button battery appears similar to a coin on plain chest radiographs but can be distinguished by a radiolucent halo and notch on anteroposterior and lateral neck views [7]. Complications resulting from battery ingestion depend upon the state of the battery, whether it is intact or damaged, the size and type of battery, and the duration and location of impaction.…”
Section: Discussionmentioning
confidence: 99%
“…These include button batteries, toothpicks, and safety pins. [15][16][17][18] Focus has been on identifying disc or button batteries in the esophagus radiographically given their propensity to cause injury there. 17 Some foreign bodies have been implicated in perforation and chronic inflammation of the gastrointestinal tract and as causes of appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Focus has been on identifying disc or button batteries in the esophagus radiographically given their propensity to cause injury there. 17 Some foreign bodies have been implicated in perforation and chronic inflammation of the gastrointestinal tract and as causes of appendicitis. Toothpicks have been found to cause acute and chronic abdominal pain with ulceration of the duodenum around the embedded wooden foreign bodies.…”
Section: Discussionmentioning
confidence: 99%